Sources with calcium and magnesium in the chemical attributes of an Oxisol and soybean yield - Firmano, Ruan Francisco; Melo, Thadeu Rodrigues de; Jordão, Luiz Tadeu; Fregonezi, Gustavo Adolfo de Freitas; Barzan, Renan Ribeiro (Scientia Agraria Paranaensis, 2017)
<span style="font-size: 10pt; font-family: ’Helvetica’,sans-serif; mso-fareast-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-family: ’Times New Roman’;" lang="EN-US">Despite the national fertilizer market increasingly present innovations, the poor product positioning with Ca and Mg prevents the improvement and balance of soil fertility conditions in soybean producing regions. This study aimed to evaluate the effect of surface application of sources with calcium and magnesium over the soil chemical attributes, grain weight, and soybean yield. The experiment was conducted during 2013/14 season, in a eutrophic OXISOL with twelve years in no tillage system in the area belonging to the School Farm of the Londrina State Universtiy (UEL), Londrina, State of Paraná. The treatments were constituted by surface application of limestone (40% CaO; 2% MgO), mixed mineral fertilizer with correction features (54% CaO; 1% MgO; 4% SiO2), fluid fertilizer (25% CaO; 10% MgO) and control (no application), in a randomized block design with six replications. The soil chemical properties were determined at 134 days after treatments application, along with productivity and weight of 100 grains (g) of soybean. The data were submitted to ANOVA and comparison of means with Tukey test at 5%. The calcium content at 0.00 to 0.05 m was raised with the application of mixed mineral fertilizer and fluid fertilizer, while potassium content was reduced with the last one. The mass of 100 grains was higher with the products that raised calcium content. In soils with high levels of exchangeable bases, the sources evaluated do not bring great benefits to soybean cultivation in a term.